MENINGKATKAN KEMAMPUAN MENGHAFAL SURAH AT-TIIN MELALUI METODE DRILL BAGI SISWA KELAS IV SD - Tri Wuryani (Universitas Tanjungpura, 2022)
In the PAI learning process in Class IV-B SDN 14 Sungai Kakap, on Quran d-Hadith, most students have not memorized the short Surah At-Tiin. Therefore, it is necessary to improve the learning method through drill method. The purpose of this research is to improve the ability of memorizing the short surah At-Tiin using the Drill Method for class IV-A students at SDN 14 Sungai Kakap. This research was carried out at SD Negeri 14 Sungai Kakap in grade IV-A odd semester, in the academicyear 2021/2022 from August to October 2021. The research subjects. are 23 students of class IV-A. The research was carried out in two cycles with four stages, namely planning, acting, observing, and reflecting. From the result of learning activities which has been carried out in three cycles and based on all the discussions and analyzes carried out, it can be concluded as follows a) after the implementation of the drill method the students in memorizing the short surah At-Tiin can improve. b) the students' abilities in memorizing the surahs improved and it can be seen from the results of thememorization test in the first cycle which was still 46% who memorized and who have not memorized 54%. The improvement was made in the second cycle, it increased the students who memorized to 71% students; and there are still 29% of students who have not memorized for the have not reachedthe target of 75%. Then improvement was also made in the third cycle, there was an increase that the students who memorized 81% and those who 19% still haven't memorized. This is considered reasonable because of the diverse abilities of students with their own faced problems.